2019
DOI: 10.1155/2019/8187529
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Lipoic Acid Protects Cardiomyocytes against Heat Stroke-Induced Apoptosis and Inflammatory Responses Associated with the Induction of Hsp70 and Activation of Autophagy

Abstract: Heat stroke (HS) is a life-threatening illness and defined as when body temperature elevates above 40°C accompanied by the systemic inflammatory response syndrome that results in multiple organ dysfunctions. α-Lipoic acid (ALA) acts as a cofactor of mitochondrial enzymes and exerts anti-inflammatory and antioxidant properties in a variety of diseases. This study investigates the beneficial effects of ALA on myocardial injury and organ damage caused by experimental HS and further explores its underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The results of ROS and JC-1 assays were in line with the mechanistic studies in humans when heat stroke occurs, such as in heat stroke, cells in the body are in a hypoxic state, ATP is reduced, Ca 2+ concentration is increased, followed by elevated ROS and oxidative stress, leading to apoptosis, tissue necrosis and autophagy, and eventually multi-organ dysfunction and individual death [23][24] . Interestingly, the results in this experiment showed that ROS was elevated and mitochondrial activity was reduced when hADSCs cells were in a high temperature environment; the cell membrane depolarization was severe during JC-1 staining, which may also lead to dysregulation of Ca 2+ flow.…”
Section: Discussionsupporting
confidence: 61%
“…The results of ROS and JC-1 assays were in line with the mechanistic studies in humans when heat stroke occurs, such as in heat stroke, cells in the body are in a hypoxic state, ATP is reduced, Ca 2+ concentration is increased, followed by elevated ROS and oxidative stress, leading to apoptosis, tissue necrosis and autophagy, and eventually multi-organ dysfunction and individual death [23][24] . Interestingly, the results in this experiment showed that ROS was elevated and mitochondrial activity was reduced when hADSCs cells were in a high temperature environment; the cell membrane depolarization was severe during JC-1 staining, which may also lead to dysregulation of Ca 2+ flow.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, the volcano and heatmap of differentially expressed mRNAs of heat shock protein (HSP) family in the spinal cords of SARM1 f/f mice and SARM1 Nestin -CKO mice showed that the level of stress-inducible heat shock 70 kDa protein (HSP70) 56 , 57 , Hspa1, was increased in spinal cords of SARM1 Nestin -CKO mice (Figure 7 D-E). HSP70 has been reported to downregulate the NF-κB signaling pathway in several disease model 58 - 60 . Further western blot confirmed the increased expression of Hspa1 in spinal cord tissues of SARM1 Nestin -CKO mice 3 d after SCI (Figure 7 F-G).…”
Section: Resultsmentioning
confidence: 99%
“…JNK pathway was not dysregulated, which indicated that the downregulation of neuroinflammation by SARM1 conditional knockout after SCI was independent on JNK pathways. Several previous studies have shown that HSP70 exhibits an immunosuppressive activity via, e.g., downregulation of NF-κB pathway activation in disease model such as Parkinson's disease 58 - 60 . Thus, we speculate that conditional knockout of SARM1 may inhibit the neuroinflammation through induction of HSP70, which may downregulate NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, activated AKT directly phosphorylates TSC2, leading to increases in a small protein, the RAS-like GTPase RHEB levels, which results in mTOR activation and autophagy inhibition [25]. It has been shown that activation of autophagy is one of the protective mechanisms against neuronal and myocardial damages in HS [10,36]. In the present study, pretreatment of EP demonstrated enhancement of autophagy activation during heat stress, evidenced by attenuation of phosphorylated mTOR (p-mTOR) and p-AKT, and increases in p-AMPK, ULK1, ATG7 and ATG12 levels, suggesting that the beneficial effect of EP is mediated via preserving the adequate function of autophagy to maintain cellular homeostasis during HS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to confer a protective effect in heat stress [9]. Our previous study has indicated that impaired autophagy function is involved in the process of HS-induced myocardial injuries, and restoration of autophagy prevents the deleterious effects [10]. Another stress protein heme oxygenase-1 (HO-1) is the inducible HO isozyme and transcriptionally upregulated in response to heat stress.…”
Section: Introductionmentioning
confidence: 99%